Asepsia vaginal prequirúrgico como prevención de morbilidad infecciosa puerperal en pacientes sometidas a cesárea - Cruz Saavedra, Esthefany Yuriko (2019)
Introduction: The puerperium is a stage characterized by a series of general and local changes, which could determine a series of complications if women do not receive the corresponding and timely attention, causing high rates of maternal morbidity, usually of infectious origin. such as puerperal endometritis and operative site infections Objective: Determine whether pre-surgical vaginal asepsis reduces the risk of puerperal infections in patients undergoing Cesarean at the regional teaching hospital of Trujillo in the 2018-2019 period. Method: This study corresponds to a prospective, cohort, analytical study with two groups of patients. Exposed group: Pregnant women with cesarean section who underwent pre-surgical vaginal asepsis. Group not exposed: Pregnant women with cesarean section intervention. which did not undergo pre-surgical vaginal asepsis, and the results of each group were analyzed. Conclusion: Vaginal asepsis reduces the risk of puerperal infection in patients undergoing Cesarean section in the Regional Teaching Hospital of Trujillo